Play and teaching in early childhood classrooms : perspectives and practices of teachers and children in South Africa - Phajane, Masello Hellen (Penerbit Universiti Kebangsaan Malaysia, 2019)
In this study, a descriptive qualitative approach was followed to explore early childhood teachers’ perspectives and practices about using play as a means of teaching in classrooms. This qualitative research study is guided by two research questions, (i) What do early childhood teachers see as the benefits of play as a means to learning. (ii) What do early childhood teachers see as obstacles to using play as a means to promote learning? The subjects of the study were all randomly selected early childhood teachers in a rural area of Bojanala Region of North West Province in South Africa. Data was collected through observations and interviews (individual and focus group). The total number of four randomly selected participants took part in the research, according to the socio-economic status of their school. Findings of this research study of the conducted classroom observations revealed that teachers; defined play differently, large enrolment and inadequate resources had a negative influence on children’s play habit and are a challenge to teachers and encountered obstacles using play as a curricular tool. Their daily routine activities and practices indicated a lack of proper guidance and support. It was also confirmed during teachers’ interviews that, teachers worked on their own without any classroom support or guidance. Based on the findings of this study, implications for the early childhood practices are deliberated and recommendations for future research are suggested.